KRISHNA AND ARJUNA: A MODEL OF GURU-SISHYA RELATIONSHIP - D'Souza, Mervyn C (Journal of Dharma, 1986)
The guru-sishya relationship plays a central role in the development and transmission of Hinduism; its roots go back to the Vedic period, wherein the guru, occupying a hermitage as a vanaprastha+ lived with his students. The Vedas describe the guru as the source and inspirer of the knowledge of the Self and as the one who blesses the disciple and enhances his spiritual life.